Algebraic formulae

  1. (a + b)2 = a2 + b2 + 2ab

  2. (a - b)2 = a2 + b2 - 2ab

  3. (a + b)3 = a3 + b3 +3a2b + 3ab2   or a3 +  b3+-3ab (a + b)

  4. (a - b)3 = a3 - b3 -3a2b + 3ab2   or  a3 - b3 -3ab (a – b)

  5. (a - b)2    =  (a + b)2  = 2a2 + 2b2

  6. (a + b)2   =   (a - b)2   = 4ab

  7. If a+b+c =0 then  a3 + b3+ c3 = 3abc

  8. (a+b) (a-b) = a2  - b2

  9. (a +b +c)2 = a2 + b2+ c2 +2ab +2bc +2ca

  10. a3 + b3+ c3 -3abc = (a +b +c) (a2 + b2+ c2 -ab-bc-ca)

  11. (x + a) ( x + b) = x2 + ( a + b)x +ab

  12. a2 + b2 = (a + b)2 – 2ab  or a2 + b2 = (a - b)2 + 2ab 

  13. a3 – b 3  = (a - b) (a2 +  ab + b2)

  14. a3 + b 3  = (a + b) (a2 -  ab + b2)